Analisis Fenomena Penunjukkan Penjabat Kepala Daerah Provinsi Aceh oleh Pemerintah Pusat - Iqbal Ahmady; Annisah Putri; Nong Ayu Triyanti Utami Hakim (Journal of Governance and Social Policy, 2023)
The phenomenon of the appointment of acting regional heads by the central government to fill the vacancies caused by the postponement of regional elections to the upcoming 2024 simultaneous regional elections has had a serious political impact. This paper will try to look at: First, discuss the problems of appointing acting regional heads related to the mechanism of the appointment process in general from the Indonesian scale and a special analysis of phenomena in Aceh Province. Second, discussing the pros and cons of the phenomenon when serving as a leader who then sees its relevance to the concept of democracy. Then, it will provide an evaluative description of the impacts that may arise so that conclusions and recommendations can be drawn for the running of an effective and efficient government in the future. This research is normative research using qualitative methods with a case study approach. Based on the results of the analysis of the findings with the theory used, the phenomenon of the appointment of acting regional heads by the central government is proven to be contrary to the concepts and principles of democracy, where procedurally the position is obtained through determination not election by the people. The recommendations put forward are that it is necessary to formulate a regulation that specifically regulates this matter and there is a need for the involvement of stakeholders in the regions to create an effective and efficient regional government.Fenomena penunjukan penjabat kepala daerah oleh pemerintah pusat untuk mengisi kekosongan jabatan yang disebabkan oleh penundaan pilkada menuju pilkada serentak 2024 mendatang melahirkan dampak politik yang serius. Tulisan ini akan berusaha melihat: Pertama, membahas problematika pengangkatan penjabat kepala daerah terkait mekanisme proses penunjukannya secara umum dari skala Indonesia dan analisis khusus fenomena di Provinsi Aceh. Kedua, membahas mengenai fenomena pro dan kontra saat menjabat sebagai pemimpin yang kemudian melihat relevansinya dengan konsep demokrasi. Kemudian, memberikan gambaran yang bersifat evaluatif dari dampak yang mungkin muncul, sehingga dapat ditarik sebuah kesimpulan serta rekomendasi untuk jalannya pemerintahan yang efektif dan efisien di masa yang akan datang. Penelitian ini merupakan penelitian normatif yang menggunakan metode kualitatif dengan pendekatan studi kasus (case study). Berdasarkan hasil analisis temuan dengan teori yang digunakan, maka fenomena penunjukkan penjabat kepala daerah oleh pemerintah pusat terbukti bertentangan dengan konsep dan prinsip demokrasi, dimana secara prosedur jabatan tersebut diperoleh melalui penetapan bukan pemilihan oleh rakyat. Rekomendasi yang diajukan adalah perlu disusun sebuah regulasi yang secara spesifik mengatur hal tersebut dan perlu adanya keterlibatan stakeholder di daerah agar tercipta pemerintahan daerah yang efektif dan efisien.